2018
DOI: 10.1101/gad.316711.118
|View full text |Cite
|
Sign up to set email alerts
|

Laminating the mammalian cortex during development: cell polarity protein function and Hippo signaling

Abstract: During mammalian brain development, radial glial progenitors balance between proliferation and differentiation to generate the laminated cortical layers in a temporally precise fashion. Defects in the individual steps going into this complex organogenesis can result in cortical malformations and human nervous system disorders. In this issue of , Liu and colleagues (pp. 763-780) present experimental evidence that an evolutionarily conserved cellular polarity gene, (), controls the balance of radial glial prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Such bRG cells are more abundant in the developing human cortex than in other primates, and this is hypothesized to contribute to cortical expansion in evolution [49][50][51] . Prior studies have demonstrated that cultured NSCs exhibit features of apicobasal polarity in culture, 52,53 and we observed this in our culture system, as NSCs form rosette structures with inward-facing apical junctions marked with PARD3 by day 9 of NSC induction (Fig. 4B).…”
Section: Har Perturbations Disrupt the Expression Of Genes Involved I...supporting
confidence: 80%
“…Such bRG cells are more abundant in the developing human cortex than in other primates, and this is hypothesized to contribute to cortical expansion in evolution [49][50][51] . Prior studies have demonstrated that cultured NSCs exhibit features of apicobasal polarity in culture, 52,53 and we observed this in our culture system, as NSCs form rosette structures with inward-facing apical junctions marked with PARD3 by day 9 of NSC induction (Fig. 4B).…”
Section: Har Perturbations Disrupt the Expression Of Genes Involved I...supporting
confidence: 80%
“…5 To date, a large number of such signals have been identified. 20,[49][50][51][52] In this review, these signals are classified into five subgroups: cell polarity, mechanical cues, cell density, soluble factors, and stress signals [53][54][55][56][57] (Fig. 3).…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…In the epithelium, PARD3 is localized to tight junctions in the Par complex, forming the boundary between the apical and basolateral domains. It plays a role in processes such as maintaining asymmetric cell division, apical basal polarity, and directional cell migration (Abdi and Kuo 2018;Li, et al 2019). It is well known that PARD3 is an important gene regulating polarity, and loss of cell polarity is a feature of advanced and aggressive cancers.…”
Section: Discussionmentioning
confidence: 99%